Experimental soft‐sediment deformation caused by fluidization and intrusive ice melt in sand. Issue 3 (25th November 2018) - Bertran, Pascal; Font, Marianne; Giret, Arnaud; Manchuel, Kevin; Sicilia, Deborah
Abstract: Identifying the driving mechanisms of soft‐sediment deformation in the geological record is the subject of debate. Thawing of ice‐rich clayey silt above permafrost was proved experimentally to be among the processes capable of triggering deformation. However, previous work has failed so far to reproduce similar structures in sand. This study investigates fluidization and intrusive ice formation from soil models in the laboratory. Experimental conditions reproduce the growth of ice‐cored mounds caused by pore water pressure increase during freeze‐back of sand in a permafrost context. Excess pore water pressure causes hydraulic fracturing and the development of water lenses beneath the freezing front. Later freezing of the water lenses generates intrusive ice. The main structures consist of sand dykes and sills formed when the increase in pore water pressure exceeds a critical threshold, and soft‐sediment deformations induced by subsidence during ice melt. The combination of processes has resulted in diapir‐like structures. The experimental structures are similar to those described in Pleistocene sites from France. These processes constitute a credible alternative to the seismic hypothesis evoked to explain soft‐sediment deformation structures in other European regions subjected to Pleistocene cold climates.